RIBIERSE-Cyted: Network for the Large-Scale Integration of Renewable Energies in Electrical Systems) – Results for 2024 - Medina Quesada, Maria de los Angeles; Montoya Giraldo, Oscar Danilo; Baier Fuentes, Carlos Rodrigo; Gil González, Walter Julián; Hernández, Jesús de la Casa (Ingeniería, 2025)
The RIBIERSE-CYTED network, i.e., the Network for the Large-Scale Integration of Renewable Energies in Electrical Systems (723RT0150; 2023-2026), is a hub for researchers and technologists attached to Ibero-American universities, companies, and local administrations. From a scientific and technical perspective, this network contributes to the decarbonization of the electricity sector by favoring the large-scale integration of renewable sources into electric power systems. It promotes and articulates a framework for joint university-business cooperation and scientific research with a shared Ibero-American vision, and it encourages knowledge of the renewable context from service providers to end users.